Perceptions of third-year mainstream students towards authentic listening materials in news sharing assignment - Ngô, Thu Phương (ĐHQGHN, 2020)
In light of communicative language teaching, authentic listening materials have been encouraged in the English as a Foreign Language (EFL) classroom, to provide a sense of realism for learners. Unlike earlier studies on students of intermediate and lower levels, this paper seeks to examine that of upperintermediate English, specifically third-year mainstream students in FELTE. The present study aims at investigating the perceptions of students towards authentic listening materials’ influences, in terms of students’ participation and their listening comprehension improvement. Participants of this research includes 116 survey respondents selected by convenience sampling method, and 4 interviewees chosen by maximum variation sampling. In order to take advantage of both quantitative and qualitative data, the researcher adopted convergent parallel mixed-methods design that yield several important results.